Development of a Minimum Competency Assessment (AKM ) Based on a Computer Based Test ( CBT ) to Measure Scientific Literacy and Numeracy Abilities - Wulandari, Anggun; Sudarmin, Sudarmin; Subali, Bambang; Saptono, Sigit (Unnes Science Education Journal, 2024)
The Minimum Competency Assessment (AKM) is a measure of literacy and numeracy achievements, which is used to map the quality of education in Indonesia against international standards. To achieve the demands of the 21st century, one important aspect is assessment. Computer Based Testing (CBT) can be used as a solution for conducting digital assessments. This research aims to determine the quality and feasibility of the AKM instrument for scientific literacy and numeracy. This research method is R&D with the ADDIE type. This research sample used a purposive sampling technique with a sample of 100 students. Expert Validation is carried out by 5 validators. The results of the research show that the development of CBT-based A K M to measure scientific literacy and numeracy skills has very good quality with the average result obtained for scientific literacy being 4.66 and numeration obtaining an average validation score of 4.77. with the "very good" category. The results of the analysis of scientific literacy question types for the average multiple choice question type were 4.8, complex multiple choice 4.7, matching 4.7, description 4.9, and short essay 4.8 with statements of very good/valid quality. Meanwhile, the results of the analysis of numeracy question types for multiple choice question types averaged 4.6, complex multiple choice 4.4, matching 4.6, description 4.7, and short essay 4.7 with a statement that the quality of the five question types was very good/ valid. The feasibility of the AKM Scientific Literacy and Numeracy Instrument was obtained from the validity analysis of the 25 items. The results of the analysis using SPSS show that the number of valid questions is 21 questions in the Eligible category.